Strategic management for logistics and supply chain operation in healthcare - I Syahrir; Suparno Suparno; I Vanany (IPTEK Journal of Proceedings Series, 2018)
In the healthcare industry, supply chain and logistics management are an important element in supporting the sustainability of the healthcare business. Business continuity in the healthcare industry requires improved quality of the healthcare sector. The quality of healthcare services may be affected by the performance of supply chain and logistics. Supply chain and logistics processes provide a substantial contribution in the overall financing of healthcare. The high costs incurred to finance the activities of the supply chain and logistics in the healthcare industry providing a major challenge for healthcare management. Management is demanded to achieve quality healthcare supply chain processes at a high level that minimize operating costs and improve service quality. So that, strategy and innovation in management are needed to achieve a high quality performance of supply chain and logistics in the healthcare industry in order to run effectively and efficiently. This paper discusses the research that focuses on the strategic management in the field of supply chain and logistics management in the healthcare industry. Based on obtained and selected articles will discuss various strategies and innovation within the healthcare system to improve supply chain performance.